PROPOSED CUSTOMER LOYALTY STRATEGY BY INCREASING CUSTOMER ENGAGEMENT AND TRUST (The Indonesian Journal of Business Administration, 2021)
Creative industry is a buffer of Indonesia's economy and a contributor to the country's GDP. In 2018 the footwear creative industry in Indonesia succeeded in producing 1.41 billion pairs of shoes or contributed 4.6 percent of total world shoe production. MKS Shoes is one of local footwear brands located in Bandung which sells shoes for women, particularly from millennials generation as its main target market. Unfortunately, the millennials generation is known having disloyal attitude and hard to trust a brand. Currently, MKS Shoes has low repeat purchase level and also fluctuates sales, which indicates customers’ low loyalty to the brand. Accordingly, the objective of this study is first, to investigate the extent to which millennials engagement could influence customer loyalty toward MKS Shoes; second, to investigate the role of millennials trust on customer loyalty toward MKS Shoes; and third, to develop loyalty strategy for millennials customers as an effort to increase MKS Shoes sales performance. This study used mix method of qualitative and quantitative research to asses external and internal environments of MKS Shoes. Qualitative method was conducted through interview with MKS Shoes management and by collecting data from journal, website and e-book. Quantitative method was conducted through survey to 228 respondents that represent customers of MKS Shoes. External analysis using PESTLE analysis, Five Porter Forces, competitor analysis and customer analysis generates opportunities and threats for MKS Shoes; while internal analysis using RBV, VRIO, STP and Marketing mix analysis reveals the strengths and weaknesses of MKS Shoes. Then, SWOT analysis and Fishbone analysis identified the root causes of low customer loyalty, which was categorized into millennials trait and behavior, rivalry and substitution, price range similar to competitors, and similarities in promotion channels. Accordingly, this study conducted Porter Business Strategic and TOWS Matrix analysis to generate 11 business solutions that could eliminate the root causes of problem. As the result, this study has developed loyalty strategy to increase customer loyalty through millennials engagement and trust toward MKS Shoes. Keywords: customer loyalty, customer engagement, customer trust, local women shoes